Quality of Wordwall-Assisted Physics Learning Outcomes Assessment Instrument - Diani, Faizatul (PILLAR OF PHYSICS EDUCATION, 2024)
The instruments used in research must meet the criteria for instrument feasibility so that accountable data is produced. The feasibility of the instrument can be measured by means of a trial. Through trials, the validity and reliability of the instrument can be determined. This research aims to develop a physics learning outcomes test instrument assisted by wordwall. To achieve the research objectives, we used research and development (R&D) model of 4D design (Define, design, development, dissemination). The instrument develop was a multiple choice test consisting of 15 items. The subject of trial involved 30 students of class X SMAN 1 Tanjung Mutiara. Based on the results of the trial 13 of the 15 items of the instrument proved to be valid with the value of tcount > ttable = 2,05 which means it meets the valid criteria. The results of the reliability test measurement of 13 instrument items obtained a value of 0,72 which means it has high reability. Based on the findings of validity test and reability test, it is conclused that the instrument development has met the feasibility to measuring the physics learning outcomes on global warming material.